POTENTIAL THREATS TO THE LEGITIMISATION OF NEPAD IN - Setlogelo, Matthews Mosimanegape (My University, 2011)
There is a large body of literature on NEPAD and much of it contends that it lacked participation and that it was a neo-liberal document which was constructed outside of the framework of the OAU. Potential threats to the legitimization of NEPAD in South Africa, is the subject of study and the primacy of public participation constituted the principal focus of this research. Nonrandom, in-depth interviews were held with research participants to test the credibility of these claims. The outcome of this study, found that much of what is written on the NEPAD process in South Africa, does not acknowledge the participatory and consultative nature of the African Renaissance and neither is it acknowledged that it formed the basis of the construction of the MAP document. It was also established that the preparation of MAP for its tabling at the OAU, did not involve organs of civil society due to the limitations of continental public policy-making processes. It is recommended that the extent of popular participation in prior processes that led to the construction of MAP and the role of the country chapters of the African Renaissance in conducting consultations with civil society required further research. The overall conclusion of this research was that the legitimacy of the NEPAD document was not undermined, and that “…it should be acknowledged that the NEPAD process was initiated by democratically elected African leaders. Such legitimacy confers responsibility to provide a vision for the continent” (Ohiorhenuan, 2001: 7).
MM - P&DM
Keywords: NEPAD